MEMBANGUN KESADARAN KOLEKTIF: PT. ABABIL GROUP LAMONGAN MENGINISIASI GERAKAN DONOR DARAH UNTUK KEMANUSIAAN - Nawari Nawari; Rifky Ardhana Kisno Saputra; Mohamad Afif Chumaedi Charis; Ahmad Sananil Nafisa; Ahmad Afri Rozikin; Kuncoro Prastyo; Saddam Rizky Andhika (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
Ababil Group Lamongan is a company that is not only engaged in business, but also has a high commitment to social responsibility. One form of community service carried out is blood donation activities, which aim to help meet the need for blood in the Lamongan area and its surroundings. This activity is held as part of the company's Corporate Social Responsibility (CSR) program, in collaboration with the Indonesian Red Cross (PMI) and various related parties. Through this blood donation activity, PT. Ababil Group seeks to increase public awareness of the importance of blood donation as a form of concern for others. In addition, this activity is also expected to help patients who need blood transfusions due to various medical conditions. Active participation from employees, partners, and the general public shows that this activity has received a positive response and contributes to building social solidarity. With this blood donation program, PT. Ababil Group Lamongan not only plays a role in the business world, but also becomes part of a real social solution. It is hoped that this activity can continue to take place periodically and provide wider benefits to the community.